EFEKTIVITAS ASEAN DAN UNCLOS DALAM PENYELESAIAN SENGKETA LAUT CHINA SELATAN: STUDI KASUS FILIPINA-TIONGKOK - Shezy Solevina Putri; Bella Sai'dah Hoerul Nisa; Elly Nurlia (Jurnal Ilmiah Hubungan Internasional Fajar, 2026)
Ambiguity and the absence of autonomous sanction mechanisms within the UNCLOS structure have led to paralysis in its enforcement. Meanwhile, ASEAN is trapped in consensus paralysis due to the principle of non-intervention and internal fragmentation. The failure of peacemaking is manifested through the non-binding DOC and the stagnation of the COC. The failure of peacekeeping is manifested through the escalation of direct violence, ranging from militarization to ship collisions between the Philippines and China. Intensive interactions between structural violence through institutional paralysis, cultural violence through the legitimization of the nine-dash line, and direct violence through physical actions ultimately create an endless cycle of conflict. Thus, the achievement of positive peace as a conflict resolution is merely an illusion, so that this dispute will always be dominated by power rather than rules. Keywords — South China Sea, Effectiveness, ASEAN, UNCLOS, Conflict Resolution